“TANSI LANGUAGE” IN SAWAHLUNTO AS A RESULT OF ACCULTURATION: A Dialect or A New Language In West Sumatera? - Fikri Ridho Pambudi; Jufrizal Jufrizal (English Language and Literature, 2019)
The aim of this study was to determine whether Tansi Language in Sawahlunto is a new language kind in West Sumatra or a dialect based on sociolinguistic analysis, speech community, language attitude, and language loyalty. Type of this research is descriptive qualitative in order to describe that Tansi Language is a language or Creole which has been claimed by the previous researcher.  This research successfully determines that Tansi Language is a new language kind in West Sumatra by comparing one hundred words of Swadesh list between Tansi Language to Minangkabaunese standard Language, and supported by questionnaires and interview sheets to get the data. According to Swadesh list, Tansi Language is categorized as a language differences with percentage 73% which is the accumulation of lexical differences and sound differences. Thus, it can be concluded that Tansi Language is a new Language in West Sumatra.